Trust models in vehicular ad-hoc networks: Towards an evaluation and comparison - Fritiofsson, Michaela; Olsson, Patrik (My University, 2017)
As traffic systems are becoming autonomous, communication between vehicles, and between vehicles and other entities, are becoming a vital part of the systems. One type of technology used in this area is vehicular ad-hoc networks (VANETs). VANETs have shown promising results in numerous areas, such as dynamic routing and safety applications. However, this technology comes with several security threats, since erroneous data might lead to travel inconveniences and possibly even car accidents. By using trust models, these risks can be mitigated. Even though there exist many trust models, there is a lack of comparable evaluations, which in turn makes it difficult to determine which is the most suitable model. The goal of this thesis is to provide a foundation for future evaluations and comparisons of VANET trust models. This has been done by both finding existing trust models, and also deriving appropriate settings for evaluating trust models in the VANET domain. The methodologies that were used were a systematic mapping study and interviews with both industrial and academic representatives. 48 trust models in the domain have been found and categorized. A simulative evaluation has been shown to be the most appropriate evaluation type, and platooning was found as the most valuable application. The results can be used by future researchers that aim to either evaluate their own trust model, or ultimately evaluate other researchers’ trust models.
Keywords: Data- och informationsvetenskap; Computer and Information Science